Antihypertensive combination therapy effects on cardiac remodelling in elderly patients - L. Kh. Gadzhieva; K. A. Masuev; M. I. Ibragimova (Российский кардиологический журнал)
Aim. To investigate potential regression of left ventricular (LV) remodelling in elderly patients receiving antihypertensive combination therapy. Materials and methods. The study included 80 patients (23 men, 57 women) with arterial hypertension (AH) and different levels of cardiovascular risk, aged 60–86 years (mean age 72,4±6,5 years; median age 72 years; interquartile range 69,5–76 years). The mean AH duration was 19,6±6,8 years. All patients underwent echocardiography at baseline and 6 months after the beginning of antihypertensive combination therapy: fixeddose combinations of an ACE inhibitor and a diuretic (perindopril + indapamide), or an ACE inhibitor plus a calcium antagonist (lisinopril + amlodipine). Statistical analyses were performed using “Statistica-6.0” software package (StatSoft Inc., 1984–2001). Results. The study participants had high and very high levels of cardiovascular risk. Six patients (7,5%) had Stage II AH, while 72 (92,5%) had Stage III AH. In 60 patients (75,0%), AH was combined with coronary heart disease (CHD), in 2 (2,5%) with diabetes mellitus (DM), in 16 (20%) with CHD and DM. Isolated systolic AH (ISAH) was registered in 35 patients (44%). At baseline, echocardiography parameters were similar across clinical groups. After 6 months of combination therapy, positive dynamics of echocardiography parameters was observed: for example, left atrium size was significantly lower in patients treated with perindopril and indapamide, compared to patients who received lisinopril and amlodipine or controls. Similar findings were obtained for end-diastolic dimension and interventricular septum thickness. In contrast to the other two groups, the control group did not demonstrate any significant dynamics of end-systolic dimension (p>0,05). Patients treated with perindopril and indapamide showed the best dynamics ofLV myocardial mass index (from 121,6±16,42 to 111,0±13,59) andLV myocardial mass (from 229,2±47,91 to 204,7±51,01). In all groups, there was an improvement in diastolic function, which manifested in a significant E/A reduction. Conclusion. In elderly AH patients with high and very high cardiovascular risk, antihypertensive combination therapy was associated with a significant regression inLV remodelling. The optimal combination included an ACE inhibitor and a diuretic (perindopril arginine and indapamide).